Mass seed production of Macrobrachiummalcolmsonii (H. Milne Edwards) in syntheticbrackishwater - Soundarapandian, P; Ananthan, G; -, Kannupandi (Indian Journal of Fisheries, 2011)
Freshwater prawn Macrobrachium malcolmsonni, has potential foraquaculture. Larvae of M. malcolmsonii were reared in synthetic brackish wa-ter using commercial salts. Live (Artema nauplii, Brachionus plicatilis andMoina sp.) and artificial feeds were provided to the larvae individually and incombination. Survival was significantly higher (39.7-63%) when larvae werefed with live feeds only. Larvae fed with artificial feed showed significantlylower survival (32.3%). Survival (58 and 61%) was significantly higher whenArtemia nauplii combined together with other feeds. Despite its limitation,synthetic brackish water can be used for freshwater prawn seed production.